Investigating links between co-rumination and personality, social functioning, and emotional well-being in a representative sample of adults - Thomas F. Denson; Michelle L. Moulds; Jessica R. Grisham (PLoS ONE, 2026)
Co-rumination occurs when people discuss problems in-depth, engage in speculation about their problems, and focus on negative affect. Current evidence suggests that co-rumination involves a paradox: whilst it can strengthen relationship bonds, co-rumination can also adversely impact mood (e.g., lead to anxiety). Most of the research on this topic to date has been conducted with children and adolescents. In this survey study, we examined the correlates of co-rumination in a representative sample of 495 adult residents of the UK (aged 18–87, stratified by age, gender, and ethnicity). In regression models, well-validated self-report measures of individual differences in perspective-taking, extraversion, agreeableness, anxiety, and measures of well-being were associated with self-reported co-rumination. Structural equation modeling showed that co-rumination mediated the relationship between some of the individual difference factors and both reduced social distress (i.e., lower loneliness and improved relationships well-being) and increased anxiety. Effect sizes were typically small. In most models, age was inversely associated with co-rumination. The emerging picture, at least for adults, is that whilst co-rumination may be associated with relationship satisfaction and well-being more broadly, it is also associated with higher levels of anxiety.